Morphokinetic assessment of the blastocyst’s trophectoderm re-expansion post-warming: predictive markers for clinical pregnancy in ART - Rossella Fucci; Irene Oliva; Arianna Marcellini; Francesca Rizzello; Laura Badolato; Denise De Angelis; Paolo Evangelisti; Elisabetta Baldi; Asia Iserani; Patrizia Falcone; Maria Elisabetta Coccia (Reproductive Biology, 2026)

Surveys as a valid tool for assessing food safety knowledge amongst pregnant women in high-income countries: a rapid review - Antonella Maugliani; Francesca Baldi (Reproductive Toxicology, 2023)

Can particulate matter be identified as the primary cause of the rapid spread of CoViD-19 in some areas of Northern Italy? - Maria Cristina Collivignarelli; Alessandro Abbà; Francesca Maria Caccamo; Giorgio Bertanza; Roberta Pedrazzani; Marco Baldi; Paola Ricciardi; Marco Carnevale Miino (Environmental Science and Pollution Research, 2021)
Northern Italy was the most affected by CoViD-19 compared to other Italian areas and comprises zones where air pollutants concentration was higher than in the rest of Italy. The aim of the research is to determine if particulate matter (PM) has been the primary cause of the high CoViD-19 spread rapidity in some areas of Northern Italy. Data of PM for all the 41 studied cities were collected from the local environmental protection agencies. To compare air quality data with epidemiological data, a statistical analysis was conducted identifying the correlation matrices of Pearson and Spearman, considering also the possible incubation period of the disease. Moreover, a model for the evaluation of the epidemic risk, already proposed in literature, was used to evaluate a possible influence of PM on CoViD-19 spread rapidity. The results exclude that PM alone was the primary cause of the high CoVid-19 spread rapidity in some areas of Northern Italy. Further developments are necessary for a better comprehension of the influence of atmospheric pollution parameters on the rapidity of spread of the virus SARS-CoV-2, since a synergistic action with other factors (such as meteorological, socio-economic and cultural factors) could not be excluded by the present study. Graphical abstract

Evaluation of foaming potential for water treatment: limits and developments - Maria Cristina Collivignarelli; Marco Carnevale Miino; Francesca Maria Caccamo; Marco Baldi (Environmental Science and Pollution Research, 2020)

The LIFE PERSUADED project approach on phthalates and bisphenol A biomonitoring in Italian mother-child pairs linking exposure and juvenile diseases - Cinzia La Rocca; Francesca Maranghi; Sabrina Tait; Roberta Tassinari; Francesca Baldi; Giorgia Bottaro; Emma Buzzigoli; Fabrizia Carli; Stefano Cianfarani; Raffaele Conte; Annalisa Deodati; Amalia Gastaldelli; et al. (Environmental Science and Pollution Research, 2018)

Effects of active music therapy on the normal brain: fMRI based evidence - Alfredo Raglio; Caterina Galandra; Luisella Sibilla; Fabrizio Esposito; Francesca Gaeta; Francesco Di Salle; Luca Moro; Irene Carne; Stefano Bastianello; Maurizia Baldi; Marcello Imbriani (Brain Imaging and Behavior, 2016)

Detection of human cytomegalovirus in transbronchial biopsies from lung transplant recipients - Cristina Costa; Antonio Curtoni; Francesca Sidoti; Cinzia Balloco; Salvatore Simeone; Samantha Mantovani; Elsa Piasentin Alessio; Daniela Libertucci; Luisa Delsedime; Paolo Solidoro; Sergio Baldi; Rossana Cavallo (Archives of Virology, 2013)

Long-acting injectable risperidone and metabolic ratio: a possible index of clinical outcome in treatment-resistant schizophrenic patients - Lucia Sara Volonteri; Giancarlo Cerveri; Ilaria Francesca De Gaspari; Maria Luisa Baldi; Maria Laura Rolandi; Pietro Papa; Massimo Carlo Mauri; Claudio Mencacci (Psychopharmacology, 2010)

Evaluation of the protective effect of bovine lactoferrin against lipopolysaccharides in a bovine mammary epithelial cell line - Chiara Pecorini; Davide Sassera; Raffaella Rebucci; Francesca Saccone; Claudio Bandi; Antonella Baldi (Veterinary Research Communications, 2010)

Rock weathering creates oases of life in a High Arctic desert - Sara Borin; Stefano Ventura; Fulvia Tambone; Francesca Mapelli; Florence Schubotz; Lorenzo Brusetti; Barbara Scaglia; Luigi P. D'Acqui; Bjørn Solheim; Silvia Turicchia; Ramona Marasco; Kai‐Uwe Hinrichs; et al. (Environmental Microbiology, 2010)
Summary During primary colonization of rock substrates by plants, mineral weathering is strongly accelerated under plant roots, but little is known on how it affects soil ecosystem development before plant establishment. Here we show that rock mineral weathering mediated by chemolithoautotrophic bacteria is associated to plant community formation in sites recently released by permanent glacier ice cover in the Midtre Lovénbreen glacier moraine (78°53′N), Svalbard. Increased soil fertility fosters growth of prokaryotes and plants at the boundary between sites of intense bacterial mediated chemolithotrophic iron‐sulfur oxidation and pH decrease, and the common moraine substrate where carbon and nitrogen are fixed by cyanobacteria. Microbial iron oxidizing activity determines acidity and corresponding fertility gradients, where water retention, cation exchange capacity and nutrient availability are increased. This fertilization is enabled by abundant mineral nutrients and reduced forms of iron and sulfur in pyrite minerals within a conglomerate type of moraine rock. Such an interaction between microorganisms and moraine minerals determines a peculiar, not yet described model for soil genesis and plant ecosystem formation with potential past and present analogues in other harsh environments with similar geochemical settings.